STRATEGI PEMASARAN KERAJINAN TAPIS BERBASIS ANDROID SEBAGAI UPAYA PENINGKATAN PEMBERDAYAAN IBU-IBU RUMAH TANGGA DAN REMAJA DESA BATURAJA WAYLIMA - Kasmi, Kasmi; Dewi, Mustika; Budi, Wahyu Sulistianing (STMIK Pringsewu, 2024)
Tapis is one of Lampung's traditional products with a special pattern of gold and silver threads, the process of making tapis cloth is quite complicated and must be done manually so it takes weeks. This is what makes filter cloth a relatively expensive price. In Baturaja Village, Waylima is still limited and there is a lack of understanding about online marketing. The strategy that will be carried out in increasing production and how to market production in the digital era is by means of several stages of activities, which include preparation, market survey, production process. In carrying out the promotion, several promotional strategies will be carried out, namely Instagram, brochures, and other online media. This study aims to describe the marketing strategy of android-based filter craft as an effort to increase the empowerment of housewives and teenagers in Baturaja Waylima Village.